2002
DOI: 10.1161/01.cir.0000036369.16112.7d
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Electrocardiographic Evidence of Transmural Dispersion of Repolarization in Patients With Long-QT Syndrome Type 1 and 2

Abstract: Background-Transmural dispersion of repolarization (TDR) may be related to the genesis of torsade de pointes (TdP) in patients with the long-QT (LQT) syndrome. Experimentally, LQT2 models show increased TDR compared with LQT1, and ␤-adrenergic stimulation increases TDR in both models. Clinically, LQT1 patients experience symptoms at elevated heart rates, but LQT2 patients do so at lower rates. The interval from T-wave peak to T-wave end (TPE interval) is the clinical counterpart of TDR. We explored the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 25 publications
9
61
1
Order By: Relevance
“…13,14 Hence, both scalar measurements and principal component analysis (PCA) have been used to describe T-wave morphology and changes in T-wave morphology parameters have been associated with impaired repolarization and bad prognosis. [15][16][17][18][19][20] The relative time course of QT prolonging drugs effect on these new biomarkers has been so far poorly evaluated.…”
mentioning
confidence: 99%
“…13,14 Hence, both scalar measurements and principal component analysis (PCA) have been used to describe T-wave morphology and changes in T-wave morphology parameters have been associated with impaired repolarization and bad prognosis. [15][16][17][18][19][20] The relative time course of QT prolonging drugs effect on these new biomarkers has been so far poorly evaluated.…”
mentioning
confidence: 99%
“…Another well-investigated index of transmural dispersion of repolarization is TpTe, which was shown to be helpful for predicting the risk for lifethreatening ventricular arrhythmias (21). Furthermore, previous studies reported that prolonged TpTe was associated with ventricular arrhythmia and sudden cardiac death in patients with hypertrophic cardiomyopathy (22), end-stage renal failure (23), inducible ventricular tachycardia (24), recent MI (25), long-QT syndrome (26), operated tetralogy of Fallot (27), and Brugada syndrome (28). TpTe/QT and TpTe/QTC, relatively novel markers for repolarization abnormalities, are not affected by heart rate and body mass in contrast to TpTe (29).…”
Section: Discussionmentioning
confidence: 99%
“…Increased transmural dispersion of repolarization (TDR) is well acknowledged to underlie the genesis of TdP in LQTS (Shimizu et al 2000;Viitasalo et al 2002;Lankipalli et al 2005;Liu et al 2005). The present study showed that gap junction enhancer AAP10 is capable of preventing augmentation of TDR and suppressing TdP in a canine LQT2 model, possibly through preventing dephosphorylation of Cx43.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that amplified transmural dispersion of repolarization (TDR) plays a critical role in the genesis and maintenance of TdP in LQTS (Shimizu et al 2000;Viitasalo et al 2002;Lankipalli et al 2005;Liu et al 2005). In vitro studies have revealed that TDR is a result of significant heterogeneity in the expression of ion channels among different cell types across the ventricular wall (Antzelevitch et al 1991(Antzelevitch et al , 1999.…”
Section: Introductionmentioning
confidence: 99%